Detection of Dengue Virus Serotypes Using RT-PCR from Jakarta, Indonesia - Widiani, Nurhaida (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
This research was conducted to identify dengue virus serotypes circulating in Jakarta using the RT-PCR method. A total of 30 blood samples were used to study dengue virus serotypes circulating in Jakarta. The results of the study showed that all four dengue virus serotypes were found in Jakarta. Apart from that, cases of double infection with the dengue virus have also been found in the area, which can worsen the symptoms of the disease. RT-PCR has proven effective in detecting dengue virus with a high level of sensitivity and specificity. Early detection of the dengue virus is considered crucial in efforts to prevent and control this disease